Precision Medicine Targeting FGFR2 Genomic Alterations in Advanced Cholangiocarcinoma: Current State and Future Perspectives - Zugman, Miguel; Botrus, Gehan; Pestana, Roberto Carmagnani; Uson Junior, Pedro Luiz Serrano (Frontiers in Oncology, 2022)
Although a relatively uncommon tumor, cholangiocarcinoma is on the rise globally. Of note, most patients are diagnosed with metastatic disease, and the prognosis is poor with cytotoxic chemotherapy. Strategies targeting specific genomic alterations have demonstrated promising activity in recent years and could represent a new therapeutic avenue for these patients. In this review, we will address the biology and clinical results of FGFR inhibition in intrahepatic cholangiocarcinoma, highlighting limitations associated with treatment and discussing the use of circulating tumor DNA to detect mechanisms of resistance.